Analisis Tingkat Pemahaman Mahasiswa Akuntansi terhadap Konsep Dasar Akuntansi Berdasarkan Asal Sekolah - Rusmita, Sari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2012)
Purpose of this study was to improved empirically about differences of understanding and comprehension of students come from SMK majoring in accounting, IPS high schools and IPA high schools against of the basic concepts of accounting. The sample in this study are 161 students majoring in Accounting, Fakultas Ekonomi UNTAN which is listed as an active second semester students for the academic year 2012/2013 and has completed the introductory to accounting course part 1. This study uses Analysis of Variance (ANOVA) test to measure differences of understanding and comprehension of students come from SMK majoring in accounting, IPS high schools and IPA high schools of the basic concepts of accounting. Results showed that there is significant difference of understanding and comprehension about basic concepts of accounting between students come from SMK majoring in accounting and IPS high schools. However, there is no significant difference of understanding and comprehension between group of students that come from IPA high Schools and IPS high schools and between students group of students that come from SMK majoring in accounting and IPA high schools.